STUDY OF GENERALISED ANXIETY DISORDER AND FACTORS AFFECTING IT DURING POSTNATAL PERIOD. - Manish Tiwari,; Pise, Harshal N; Mahima Tiwari, (Asian Journal of Pharmaceutical and Clinical Research, 2022)
ABSTRACT Background: Anxiety disorders remain the commonest mental disorder in general population. Both these disorders are common in pregnant women and postpartum period and are underdiagnosed. There is a paucity of research on mental disorders and their risk factors among women during postnatal period in India. This study aims to estimate the incidence of generalised anxiety disorder (GAD) and depression and explore the common associated factors among postnatal women in India. Aim: The present study aims to study the incidence and risk factors of generalised anxiety disorders among mothers attending the outpatient department clinic (OPD) for vaccination of their children or gynaecology OPD for follow up. Methods: Total of 180 women of postpartum period, up to 6 months, was randomly selected and assessed using self-report questionnaire GAD-7 for GAD. General demographic details were obtained via a revalidated proforma. Incidence and risk factors for both these mental disorders were assessed. Results: The incidence of GAD was found to be 31.11%. Primigravida mothers scored higher on GAD-7 score than multigravida mothers and incidence of GAD was also higher in primigravidas mothers (p=0.042). There was no significant association between age of mother, socioeconomic status of mother, and sex of the child born, with development of GAD in the postnatal period. Substance abuse in husband was significantly related to development of GAD in women in postnatal period. Conclusion: A significant proportion of women had generalised anxiety disorder. Pregnancy for the first time was associated with increased risk of GAD. Substance abuse by husband is significantly associated with development of GAD and depression during postnatal period.